Membangun dan Menggali Inspirasi Anak Muda Melalui Literasi dan Semangat UMKM - Ratnawati, Indah Ika; Putri, Nanda Adelia; Pasha, Sesilia Azizah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
The Community Service Program (Kuliah Kerja Nyata or KKN) is an initiative by Universitas Balikpapan students to contribute positively to society. The KKN program in Graha Indah Subdistrict, North Balikpapan, focuses on literacy development and the empowerment of Micro, Small, and Medium Enterprises (MSMEs). One of the primary initiatives, the MSME Literacy Corner, aims to enhance community literacy across multiple aspects, including reading and writing, digital literacy, and business literacy. In the modern digital era, literacy extends beyond basic reading and writing skills to include technological proficiency, information analysis, and digital business strategies. This program seeks to provide MSME actors in Graha Indah with the necessary understanding to develop their businesses more effectively. Beyond MSME support, the Literacy Corner also addresses education and social awareness by fostering reading interest among youth through the establishment of an educational reading corner. Additionally, various social activities were conducted, including community religious gatherings, administrative assistance at the subdistrict office, and participation in local events such as the commemoration of Isra Mi'raj and MSME bazaars. By engaging in these diverse community activities, this program aspires to leave a lasting impact while simultaneously providing valuable practical experiences for students. The KKN MSME Literacy Corner serves as a starting point to cultivate a literacy culture and prioritize knowledge acquisition for both business and personal development.